Functional rehabilitation of heritage buildings based on reinforced concrete structural elements. Cultural/historic values and public utility to consider - Miranda Dias, J. (2017)
For the definition of conservation and rehabilitation actions in buildings of heritage value, it is necessary to take into account the significant evolution processed in several functional aspects of these buildings. The complexity of the issues involved in conservation and repair of their construction elements and functional rehabilitation requires knowledge in several domains, in order to integrate, in an interdisciplinary and multidisciplinary way, the functional requirements that are needed to be considered. This article focuses attention on the buildings classified as cultural heritage as well as buildings not included in this classification, but which present relevant cultural/historical value or public utility. In both cases targeting the set of buildings that are specifically based on structural concrete elements associated to infill or resistant masonry walls. Relevant aspects of the overall performance of referred heritage buildings are here presented, in particular of their walls and confining elements, concerning the different basic requirements and the other functional requirements.